How Digital Services are changing the work dynamics in Community Health Centers or the Health Sector : A Comprehensive Review For Future Research agenda - Andrias Andrias; Setyo Riyanto; Dewi Nusraningrum; Muhammad Ali Iqbal (Universitas Diponegoro, 2026)
The digital transformation in the healthcare sector, often referred to as the